Angiogenesis in Ischemic Stroke Patients Aged 30 - 80 years at Gatot Subroto Army Central Hospital (RSPAD) Jakarta - Hidayat, Andri; Arief, Mansyur; Wijaya, Andi; As’ad, Suryani (BALI MEDICAL JOURNAL, 2016)
Background: Angiogenesis, is one of the neurorepair process which plays an important role after ischemic stroke incident. vascular-endothelial growth factor (VEGF), Angiopoietin-1 (ANG1) and fibroblast growth factor (FGF) are the angiogenic factors involved in the process of angiogenesis. In this study we observed VEGF, ANG1 and FGF concentration to represent the angiogenesis process occurred in ischemic stroke patients with different onset time. Methods: This was a cross sectional study involving 63 ischemic stroke subjects aged 30 – 80 years old from The Central Hospital of the Army (RSPAD) Gatot Subroto Jakarta. Subjects were divided into 3 groups due to stroke onset time.: < than 7 days (Group A: 11 subjects), onset 7 – 30 days (Group B: 26 subjects) and > 30 days (Group C: 26 Subjects). VEGF, FGF and ANG1 serum levels were measured using multiplex method with luminex Magpix instrument. Results: VEGF, ANG1, and FGF were not significantly different between all groups. We did not find any significant correlation in all groups except FGF with ANG1 in group C. VEGF and ANG1 levels found to be highest in group B, and FGF levels in group A. Conclusions: VEGF, FGF and ANG1 increased soon after ischemic injury. FGF immediately increased in first week after onset and then decreased. VEGF and ANG1 levels reach their peak levels between 7-30 days after injury, showed that the optimal process of angiogenesis occurs in this period. There is no significant correlation between VEGF, FGF and ANG1 in all groups but we found a correlation between FGF and ANG1 in subjects with onset > 30 days after injury.